Neonatal overfeeding attenuates microgliosis and hippocampal damage in an infant rat model of pneumococcal meningitis - Cassiano, Larissa Marcely Gomes; de Queiroz, Karina Barbosa; Martins, Thais Veronez de Andrade; Maia, Ana Luiza Azevedo; Rachid, Milene Alvarenga; Spencer, Sarah J.; Coimbra, Roney Santos (Frontiers in Immunology, 2024)
Background: Pneumococcal meningitis (PM) triggers apoptotic neuronal and progenitor cell death in the hippocampal dentate gyrus (DG), resulting in subsequent cognitive impairment. Microglia play a crucial role in PM-induced hippocampal damage. While the lasting effects of neonatal nutrition on health are well documented, the influence of early-life overfeeding on the host response to neuroinfections remains uncertain. This study aimed to examine whether neonatal overfeeding affects the outcome of PM in the hippocampus (HC).Overfeeding was induced by adjusting litter size immediately after birth. On the eleventh day of life, rats were intracisternally injected with Streptococcus pneumoniae or saline, followed by euthanasia after 24 hours for brain dissection. Histological analysis evaluated apoptosis in the DG and the extent of inflammatory infiltrate in the hippocampal fissure, while microgliosis was assessed by immunohistochemistry. The hippocampal transcriptome was analyzed using RNAseq, and the mRNA levels of specific inflammatory biomarkers were evaluated via RT-qPCR.Results: Overfed rats exhibited 40.5% greater body mass compared to their normal-fed counterparts.Intriguingly, PM-induced apoptosis in the DG was 50% lower in overfed rats. This effect was accompanied by significant alterations in the hippocampal transcriptional profile, particularly the lack of activation of the Programmed cell death pathway in overfed infected animals. RT-qPCR analysis of Aif1 and examination of Iba1-immunostained cells revealed mild microgliosis in the HC of infected-overfed animals. This reduced microglial reaction may be attributed to the diminished activation of interferon signaling pathways, as disclosed by the transcriptome analysis, potentially preventing microglial priming. Additionally, evidence of reduced neuroinflammation in overfed rats with PM was observed through the milder activation of pathways associated with Toll-like receptors, interleukins, and chemokine signaling. Furthermore, overfed animals exhibited increased transcription of proinflammatory Il6 and anti-inflammatory Il10 genes, with the latter showing higher expression even in the absence of PM, suggesting a priming effect of overfeeding on hippocampal immune cells.This study sheds light on the complex interplay between early-life overfeeding, immune response, and neuroprotection in infant rats with PM. The findings demonstrate the neuroprotective impact of early-life overfeeding in the context of PM, linked to the modulation of microglial function.